Teacher I. A. Serbaw and academician A. A. Shakhmatov: the history of collaboration - Vaitovich, Aliaksandra U. (Journal of the Belarusian State University. History, 2025)
The purpose of the article is to determine the main directions of cooperation between I. A. Serbaw and the authoritative linguist A. A. Shakhmatov. It is shown that the correspondence between them lasted from 1911 to 1917. Ten letters from the school teacher to the Saint Petersburg academician have survived to this day. A few messages discussed I. A. Serbaw’s official activities, while most of the letters were devoted to scientific issues. I. A. Serbaw shared with the head of the Department of Russian language and literature of the Imperial Academy of Sciences his thoughts about the peculiarities of the speech of the Poleshuks. He reported the results of the expeditions and planned further publications. A. A. Shakhmatov provided moral, material, and organisational assistance to his younger colleague. Due to the support of this authoritative linguist, I. A. Serbaw was able to implement several projects, including expeditions to Palesie in 1911 and 1913, as well as the publication of a monograph about the Belarusian sakuns.
Keywords: history of Belarusian ethnography; history of Belarusian linguistics; I. A. Serbaw; A. A. Shakhmatov; Е. A. Masalskaya- Surina; A. K. Snitko; E. R. Ramanaw; D. I. Dawgiala